Potential for increased smallholder dairying - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The World Bank has estimated that demand for milk and dairy products in sub-Saharan Africa will increase by 5.5 million tonnes by the year 2025 - a growth rate of 4% a year. Much of this demand will be concentrated in urban areas. Currently in most...